CONDUCTING DISTANCE SCIENTIFIC EXPERIMENTS IN TECHNICAL AND INFORMATION TECHNOLOGY DIDACTICS - Henryk, NOGA; SLOSARZ, Piotr (Trends in education, 2014)
A considerable technological development noticed especially in the last years has improved the access to information, thus supporting young people in broadening their scientific knowledge. However, acquiring new facts in situations when there is no possibility to visualise specific concepts might be ineffective. Even if a person interested in a given subject wanted to carry out an experiment whose function would be to connect the new theoretical and practical knowledge, as it is frequently done in the case of module learning, it would turn out to be impossible because there would be a need to apply some measuring equipment adjusted to the form of the experiment. Assuming that the purpose of the experiment is observing the influence of capacitors use in the process of electronic circuit stabilisation, there will appear a need to use an oscilloscope which costs a lot. Furthermore, sometimes a student who did not manage or for personal reasons could not conduct a given experiment during his/her classes, frequently has no possibility to do it later. Because of that more and more places of higher education decide to create special rooms prepared to enable students to carry out distance experiments, using just an access to the Internet and a browser.
Keywords: technology; distance experiment; didactics.